2017
DOI: 10.20429/ijsotl.2017.110215
|View full text |Cite
|
Sign up to set email alerts
|

Technical Drafting and Mental Visualization in Interior Architecture Education

Abstract: We explored how beginning-level interior architecture students develop skills to create mental visualizations of three-dimensional objects and environments, how they develop their technical drawing skills, and whether or not physical and computer generated models aid this design process. We used interviews and observations to collect data. The findings provide an insight on what kind of difficulties students experience during their learning process and how they overcome those difficulties. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Third, design educators should nurture students’ visualization capacity for their success in education in a way that the students’ development of spatial ability also enhances design performance. Arslan and Dazkir () found that when beginning interior architecture students experience difficulties in 2D and 3D mental visualization, many of them simply copy others’ drawings without fully grasping the visualization concept; such experiences negatively influence their design process. Potter and Van der Merwe () also found that students with low spatial ability tended to fail their graphic communication course without receiving appropriate intervention perhaps because of the disconnect between technical communication courses and creative design courses.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…Third, design educators should nurture students’ visualization capacity for their success in education in a way that the students’ development of spatial ability also enhances design performance. Arslan and Dazkir () found that when beginning interior architecture students experience difficulties in 2D and 3D mental visualization, many of them simply copy others’ drawings without fully grasping the visualization concept; such experiences negatively influence their design process. Potter and Van der Merwe () also found that students with low spatial ability tended to fail their graphic communication course without receiving appropriate intervention perhaps because of the disconnect between technical communication courses and creative design courses.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Spatial ability is an important factor that can affect success in the fields of mathematics and geometry (Battista, 1990;Bulut & Köroğlu, 2000;Guay & McDaniel, 1977;Tartre, 1990;Ünlü & Ertekin, 2017), engineering (Sorby, 1999;Sorby & Baartmans, 2000;Yue, 2008), chemistry (Bodner & Guay, 1997;Carter, Larussa, & Bodner, 1987;Pribyl & Bodner, 1987;Wu & Shah, 2004), physics (Delialioğlu & Aşkar, 1999;Kozhevnikov, Motes, & Hegarty, 2007), geology (Kali & Orion, 1996;Uttal & Cohen, 2012), architecture (Arslan & Dazkir, 2017), health, medicine and dentistry (Hegarty, Keehner, Khooshabeh, & Montello, 2009;Nguyen, Mulla, Nelson, & Wilson, 2014). Spatial ability which can affect success in various fields and can lead to significant individual differences in learning environments is often neglected in educational and instructional settings (Lubinski, 2010).…”
mentioning
confidence: 99%
“…This feature can be helpful for lectures in subjects such as architecture. Here, a building model can be presented to students virtually so that they can understand the building structure more easily and directly (Arslan and Dazkir, 2017). The availability of the features of the various online platforms is summarized in Table 1.…”
Section: Features Of Vr Collaborative Platformsmentioning
confidence: 99%